STRATEGI LEMBAGA ADAT MELAYU DUSUN MUARA KUAMANG DALAM PENYELESAIAN KONFLIK LAHAN - Ridwan Ridwan; Yuli Nopriyani (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
In the social life of indigenous Malay community has an important role, both as a basis for the action, as well as how to solve the problems. Lembaga Adat Melayu Dusun Muara Kuamang has been actively involved in land conflicts in Hamlet menyelsasikan Kuamang Estuary. This study examines the strategies of the Institute of Traditional Malay village in Muara Kuamang menyelelesaikan land conflicts in Dusun Muara Kuamang. This research was conducted in Muara Kuamang Hamlet with the research period January to April 2020. The results of the study found that customary law can be used as an alternative to conflict resolution that is more knowledgeable and prudent. Customary law is able to provide a major role in resolving land conflicts that occur in the hamlet of Muara Kuamang. Strategy Board Raya Dusun Muara Kuamang in land conflict resolution in Dusun Muara Kuamang including through mediation and custom assembly. The constraints Lembaga Adat Melayu Dusun Muara Kuamang. in the settlement of the land conflict in Dusun Muara Kuamang, that is, the disputing parties did not comply, the limitations of witnesses in the trial and the order of the trial were not complied with by the disputing parties.